The Post-Bandung Order and the Multiplex Trap: Reconsidering Indonesian Agency and the Imagination of the Global South - Utama, Virdika Rizky; Mukhtar Abdullah (JURNAL HUBUNGAN LUAR NEGERI, 2025)
The 1955 Bandung Asian-African Conference is often regarded as a historic moment that paved the way for envisioning a more equitable global order. However, after seven decades, the spirit of Bandung has been preserved more as a ceremonial symbol than actualised into a substantive agenda. Utilising Amitav Acharya's framework of the multiplex world, this article proposes the concept of the "multiplex trap" to explain the paradox of multipolarity: the presence of more great powers does not necessarily bring about the democratisation of the global order, but rather multiplies the old layers of hierarchy. In this context, Indonesia faces complex agency challenges. Its presence in various international forums—the Non-Aligned Movement, G77, BRICS, and G20—demonstrates consistent multi-layered diplomacy, but this is not enough to change the global power structure. Through a historical-structural approach and critical examination of epistemic hierarchies, this article highlights how the Global South still largely uses vocabulary formulated by old and new hegemonies, making it difficult to produce alternative norms rooted in its own experiences. Case studies, such as Indonesia's reduction of export tariffs to the United States, followed by strategic import contracts, as well as the adoption of Chinese-style digital surveillance technology by the domestic elite, demonstrate how pragmatic choices can sometimes narrow the space for autonomy. The fragmentation of interests among Southern countries, the erosion of solidarity in trade transactions, and the limited normative innovation also explain why the spirit of Bandung has not evolved into Bandung 2.0. This article offers a forward-looking reflection: Indonesia can leverage its strategic position not only as a connector between blocs, but also as a formulator of a more inclusive alternative discourse. By shifting the focus of solidarity from blocs of countries to cross-border networks—such as climate justice, migrant dignity, and digital sovereignty—and building a more contextual diplomatic vocabulary, the Bandung spirit has the potential to be revived not as nostalgia, but as epistemic empowerment for the Global South.